Foreign Assistance and Economic Development in Korea - Hong, Sokchul; Ryu, Sang-yun (KDI School of Public Policy and Management, 2020)
A large scale of foreign assistance or aid has been provided from developed to developing countries throughout the second-half of the 20th century. However, only a few countries out of beneficiaries succeeded in economic development. This has provoked a controversy over on the effectiveness of foreign assistance. Many researchers have argued that such assistance is useless, and some emphasized the significance of government’s accountability in maximizing its effectiveness (Collier 2007; Easterly 2006; Moyo 2009; Burnside and Dollar 2000, 2004). The issue is still under debate. Examining the historical experience and lessons of successful counties like Korea would be useful to learn how to improve the effectiveness of foreign assistance. Korea is one of the countries which received a lot of foreign assistance and achieved a rapid economic growth in short period. Korean War in 1950-53 devastated people’s life and infrastructure across the country. After the War, no one believed that Korea would become one of most industrialized and developed countries after 60 years. Therefore, Korean experience has been called as “Miracle on the Han River”. However, previous studies on the role of foreign aids in Korean economic development is not always favorable. Some argue that foreign aids in the 1950s and 1960s distorted economic structure in Korea and delayed economic independence (Hong 1962; Yi 1987). Some pointed out that the distribution of foreign aids was not effective (Krueger 1977; Cho 1996; Kim 1999). Nevertheless, those studies do not provide enough empirical evidence to conclude the effectiveness of foreign aids in Korea. The study aims to provide more reliable empirical evidence by looking into historical micro data on foreign aids, which have been rarely used in previous studies. In particular, this study plans to examine the role of foreign aids in industrialization in Korea. After the Korea War, US foreign assistance agencies---FOA (Foreign Operations Administration) and ICA (International Cooperation Administration)---provided aids to rebuild Korean economy. FOA/ICA aids are divided into two types: project and non-project assistance. Project aids were intended to improve social infrastructure such as sanitation, education and transportation. Non-project aids were more related to industrialization because various kinds of economic resources, including fuel, industrial raw material and machinery, was distributed among Korean industries and firms in the late 1950s and 1960s. Therefore, it is necessary to study how non-project assistance affected Korean economic development for better understanding the effectiveness of foreign aids not only in Korean perspective, but also in the general aspect of development economics. The specific questions that this study tries to answer are as follows: [1] Was the allocation of foreign aid in the 1950s competitive, fair, and efficient? [2] How much did the foreign aid in the 1950s contribute to firms’ survival and performance in later years? In the purpose of our study, it is key to have detailed information on Korean firms which received the benefit of foreign aids. Fortunately, such information was recorded in some government reports issued or received by US FOA/ICA: 1) Small Business Circular, 2) Weekly Report of Sub-authorizations, 3) Daily report on Allocation of ICA Funds. We found that those reports are available in US NARA (National Archives and Records Administration), University of Washington Library. Our research team has collected the information on those historical records with the support of KDI School of Public Policy and Management. Especially, our research team visited NARA twice, took photos of about 6,000 pages in the records, and digitized them. In addition to the micro-level data, we also collected some historical statistics on foreign aids from yearbooks of the Bank of Korea and the Korea International Trade Association and Korean business directories with firm information. In particular, we used Daily Report, which contains bidding results at the firm-level, as an important data source. I matched Daily Report with several Korean-language business directories that contain information on firm characteristics. The analysis revealed that the allocation of the major part of aid funds was more competitive and fair than what was depicted by previous research. The rule of bidding was actually implemented, which greatly reduced the room for discretionary intervention by the government or collusion among firms. The fact that larger firms were allocated more rent does not need to be interpreted as indicative of allocative inefficiency, although a more rigorous analysis is needed in order to be able to speak of the efficiency of aid with confidence. Our analysis also found out that firms that earned more rent, or in other words, a larger amount of financial benefit from the allocation of aid had a larger firm size in the early 1970s even when controlling for firm size in the late 1950s. This relationship persisted even in regression analyses using alternative variables. Such a result indicates that aid had a positive impact on the growth of Korean firms. Although the size of rent was found to have no significant effect on the firms’ rate or return, this is likely because the rate of return of a firm at a certain point of time is affected primarily by the specific characteristics of the business category or market situation rather than by its actual business competence.